Measuring direct and indirect tendon parameters to characterize the proximal tendinous complex of the rectus femoris in football and futsal players - Mechó, Sandra; Lisbona Ortega, Raquel; Pruna, Ricard; Nescolarde Selva, Lexa; Morillas Pérez, Jordi; Rodríguez-Baeza, Alfonso; Martínez Agea, Javier; Pérez-Andrés, Ricard (Frontiers in Physiology, 2023)
Objective. To present unprecedented radiological parameters to characterize the angle between the direct and indirect tendon of the proximal rectus femoris and its inclinations. To evaluate the population variability according to demographic variables. Materials and Methods. From September 2019 to July 2021, using MRI multiplanar reconstructions of proximal thigh/hip, two blinded radiologists measured the direct-indirect tendon angle and the inclination of each tendon in different planes. The intra and inter-observer agreement were assessed with Bland-Altman analysis and Intraclass Correlation Coefficient. The correlations between radiological parameters and demographic variables were evaluated using linear regression, Student’s T-test and analysis of variance. Results. Were performed 112 MRI scans of the thigh/hip on 91 football players of different age, gender, and disciplines (football and futsal). For observer 1 (the reference) the mean direct-indirect tendon angle was 56.74º ± 9.37, the mean indirect tendon slope was -7.90º ± 7.49, and the mean direct tendon slope 22.16º ± 5.88. The three measurements showed inter and intra-observer agreement (mean differences 0). No correlation was observed between age and the parameters. Likewise, no statistically significant differences were found for gender, dominant limb, examined limb, and sport. Conclusion. There is inter and intra-observer agreement in the measurements of the direct-indirect tendon angle and the inclination of each tendon. There is population variability in proximal tendinous complex unrelated to demographic factors. These results allow going a step further in the detection of morphological patterns that represent a risk factor for lesions in the rectus femoris in professional football, futsal players and other sports.